STUDENT PERCEPTION ANALYSIS ON SMART CAMPUS IN NATIONAL DEFENCE UNIVERSITY OF MALAYSIA (NDUM) - Mohd Faizal Mustafa (Tesis, 2021)
The main contribution of this thesis is to evaluate the student's perception on the smart campus from various application for each smart element.